The Vietnam War: An Analysis of History, Causes, and Impacts - Ngiêm Dương (Global Writing Academica Researching and Publishing, 2023)
The Vietnam War stands as one of the most controversial and influential military conflicts of the 20th century. This journal article aims to provide an in-depth analysis of the history, causes, and impacts of the war that raged in Vietnam from 1955 to 1975. Utilizing primary and secondary sources, the author delves into various aspects of the conflict, including its historical context, underlying reasons for its outbreak, and far-reaching consequences that continue to shape regional and global affairs to this day.The historical context of the Vietnam War can be traced back to the colonial era when Vietnam was under French colonial rule. The desire for independence and unification was a central theme that shaped the Vietnamese national identity and led to various anti-colonial movements. After the First Indochina War, which resulted in the division of Vietnam at the 17th parallel, the stage was set for further hostilities that eventually escalated into the Second Indochina War. The root causes of the Vietnam War were multifaceted and complex. One of the primary factors was the ideological divide between the communist North and the non-communist South. The Cold War rivalry between the United States and the Soviet Union also played a pivotal role, with the U.S. supporting the South Vietnamese government to prevent the spread of communism in Southeast Asia. Additionally, the role of nationalism and regional dynamics contributed to the escalation of hostilities in the region. This section explores the major events and turning points during the Vietnam War, including the Gulf of Tonkin incident, the Tet Offensive, and the Paris Peace Accords. These events had significant implications for the trajectory of the conflict and shaped public opinion both within the involved countries and internationally.